Genom-Editierung mit CRISPR/Cas9: Vorzeichen einer neuen Epoche der Medizin? - Schermer, Bernhard; Benzing, Thomas (DMW - Deutsche Medizinische Wochenschrift, 2019)
The emergence of genome editing technologies can be regarded as one of the most groundbreaking revolutions in the history of science. Modern genome editing allows the introduction of precise mutations into the genome of virtually all cells and organisms without leaving any additional trace. Undoubtedly, genome editing with CRISPR/Cas9, often casually referred to as “genetic scissors”, will revolutionize medical research and development. However, at the same time it creates a great need for ethical considerations as it might hold risks for both people and the environment that cannot yet be fully assessed. While genome editing is already well established in laboratory research, clinical applications based on genome editing are close. For the first time, targeted corrections of genetic defects in somatic cells, stem cells as well as in the germ line appear technically feasible. This generates possible future scenarios that urgently require broad ethical and social discussions.
Keywords: Genom-Editierung; Genschere; CRISPR/Cas9; Gentherapie; Bioethik